Determinants of Adaptation Strategies to Climate Change by Farmers in District Sargodha, Pakistan - Muhammad Qadeer Ashraf; Shahbaz Ahmad Khan; Rabbia Khan; Muhammad Waheed Iqbal (International Journal of Economic and Environment Geology, 2018)
Pakistan is one of the most affected countries vulnerable to climate change. Additionally, being a predominantly agricultural economy, farming community is more at risk and climate change is predicted to decrease crop yields in Pakistan as a result of higher temperature, variability in rainfall and floods. Understanding the perception and adoption strategies to climate is important to preparing farming community for climate change impact. The present study was aimed to explore determinants of adaptation strategies to climate change by farmers. The data were collected through interview schedule. Logit regression model was used to explore the factors influencing the decision of farmer adaptation strategies to climate change. The study explored that education, farming experience, annual farm income, access to television, access to extension services, access to climate change information and membership in community based organization are main factors influencing the decision of farmers to climate change adoption. The study recommends that Government must ensure extension service, climate information and credit schemes to farmers to alter the production strategies in response to climate change.